Valuing the non-market production of agriculture; Bewertung nicht-marktlicher Agrarproduktion - Michael Ahlheim; Oliver Fror̈ (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2003)
As a consequence of the negotiations for a new agricultural policy of the EU the multifunctionality of agricultural production has come into new prominence in the public. The philosophy that subsidies for the agricultural sector should be calculated not only by ag-ricultural market production but also according to agricultural non-commodity production like e.g. the conservation of the countryside, makes it necessary to assess the social value of this part of agricul-tural production. In this paper we scrutinize the welfare theoretical background of the economic valuation of non-market production as well as the existing practical valuation techniques. Further, the applicability of these techniques to the valuation of agricultural non-commodity production is considered.
Keywords: 330; Agrarproduktion; Öffentliche Güter; Zahlungsbereitschaftsanalyse; Kosten-Nutzen-Analyse; Wohlfahrtsökonomik